Impact of simulated acid rain on chemical properties of Nyalau series soil and its leachate - Mohamad Hilmi, Ibrahim; Susilawati, Kasim; Osumanu Haruna, Ahmed; Mohd. Rakib, Mohd. Rashid; Nur Aainaa, Hasbullah; Md. Tariqul Islam, Shajib (Springer Nature Limited, 2024)
Greenhouse gases can cause acid rain, which in turn degrades soil chemical properties. This research was conducted to determine the effects of simulated acid rain (SAR) on the chemical properties of Nyalau series (Typic paleudults). A 45-day laboratory leaching and incubation study (control conditions) was conducted following standard procedures include preparing simulated acid rain with specific pH levels, followed by experimental design/plan and systematically analyzing both soil and leachate for chemical changes over the 45-day period. Six treatments five of which were SAR (pH 3.5, 4.0, 4.5, 5.0, and 5.5) and one control referred to as natural rainwater (pH 6.0) were evaluated. From the study, the SAR had significant effects on the chemical properties of the soil and its leachate. The pH of 3.5 of SAR treatments decreased soil pH, K+, and fertility index. In contrast, the contents of Mg2+, Na+, SO42−, NO3−, and acidity were higher at the lower SAR pH. Furthermore, K+ and Mg2+ in the leachate significantly increased with increasing acidity of the SAR. The changes in Ca2+ and NH4+ between the soil and its leachate were positively correlated (r = 0.84 and 0.86), whereas the changes in NO3 − negatively correlated (r = − 0.82). The novelty of these results lies in the discovery of significant alterations in soil chemistry due to simulated acid rain (SAR), particularly impacting soil fertility and nutrient availability, with notable positive and negative correlations among specific ions where prolonged exposure to acid rain could negatively affect the moderately tolerant to acidic and nutrient poor soils. Acid rain can negatively affect soil fertility and the general soils ecosystem functions. Long-term field studies are required to consolidate the findings of this present study in order to reveal the sustained impact of SAR on tropical forest ecosystems, particularly concerning soil health, plant tolerance, and potential shifts in biodiversity and ecological balance.